Basic hardware module for a nonlinear programming algorithm and applications - Lin, Shin-Yeu (Automatica (Oxford), 1997)
We present a VLSI-array-processor architecture for the implementation of a nonlinear programming algorithm that solves discrete-time optimal control problems for nonlinear systems with control constraints. We incorporate this hardware module with a two-phase parallel computing method and develop a VLSI-array-processor architecture to implement a receding horizon controller for constrained nonlinear systems. On the basis of current VLSI technologies, the estimated computing time to obtain the receding-horizon feedback-control solution meets the realtime processing-system needs.